2022
DOI: 10.1101/2022.07.14.500026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulatory dynamics of periodic and aperiodic activity in respiration-brain coupling

Abstract: Bodily rhythms such as respiration are increasingly acknowledged to modulate neural oscillations underlying human action, perception, and cognition. Conversely, the link between respiration and aperiodic brain activity - a non-oscillatory reflection of excitation-inhibition (E:I) balance - has remained unstudied. Aiming to disentangle potential respiration-related dynamics of periodic and aperiodic activity, we applied novel algorithms of time-resolved parameter estimation to resting-state M/EEG data from two … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Neurotypical control population. Forty healthy volunteers (21 female, age 25.1 ± 2.7 y [M ± SD]) were used as a neurotypical control population (data from [19]). All participants reported having no respiratory or neurological diseases and gave written informed consent prior to all experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotypical control population. Forty healthy volunteers (21 female, age 25.1 ± 2.7 y [M ± SD]) were used as a neurotypical control population (data from [19]). All participants reported having no respiratory or neurological diseases and gave written informed consent prior to all experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Respiration-locked estimations of 1/f slope. We defined a parieto-occipital region of interest for movement-corrected MEG (k = 41 sensors, taken from [19]. Single-sensor time series within this ROI were entered into the SPRiNT algorithm [26] with default parameter settings and subsequently averaged.…”
Section: Head Movement Correctionmentioning
confidence: 99%
“…Stimulus onsets and responses which occurred exactly at the peak or trough were defined as relating to respiratory transitions and were not included in the respiratory state analyses, as these have been shown to represent distinct cognitive (Nakamura et al, 2018) and excitatory phases (Kluger et al, 2023), and there were too few in total (approx. 5% of total trials) to justify separate transition-based analyses (see Fig 1C).…”
Section: Analysis Behavioural and Physiological Preprocessingmentioning
confidence: 99%
“…Theoretical proposals suggest that this modulation operates by adaptive gain control through the respiratory tuning of neural excitability, a mechanism that is critical for evidence accumulation during perceptual decision-making (Allen et al, 2022;Aston-Jones & Cohen, 2005;Cheadle et al, 2014;Corcoran et The respiratory cycle modulates distinct dynamics Braendholt et al 2023 of affective and perceptual decision-making 3 al., 2018; Kluger et al, 2021). While some studies have demonstrated psychological and neural effects of the respiratory cycle that are broadly consistent with shifts in neural gain (Kluger et al, 2021(Kluger et al, , 2023, so far no study has directly examined the underlying cognitive mechanisms using computational modelling. As studies have highlighted consistent modulation of reaction time by respiratory rhythms (Johannknecht & Kayser, 2022), we hypothesised that breath-brain coupling may alter the underlying latent variables governing perceptual and affective decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation